Morphological and Morphometric Study of Pila celebensis (Gastropoda: Ampullariidae) from Madura Island, Indonesia - Hanuninda, Dewi; Ambarwati, Reni; Isnaningsih, Nur Rohmatin (Jurnal Riset Biologi dan Aplikasinya, 2025)
Pila celebensis (family Ampullariidae) is a native freshwater snail species found in Asia, including Indonesia, and possesses significant ecological and economic importance. However, Pila populations face various threats due to the invasiveness of  Pomacea, as well as human activities. This study aimed to document the presence of P. celebensis on Madura Island and describe its morphological and morphometric characteristics. Samples were collected from four localities in Madura. All specimens had a similar morphological shell, including a spherical shell with a prominent brown color and dark brown spiral pattern, an oval to elongate lunar aperture, a thin or closed umbilicus, and a concentric operculum. However, morphometric size varied significantly by location. The largest individuals were found in the rice fields of South Poter Village, while the smallest were found in a stream in Nyalabuh Laok Village. This difference reveals that environmental factors, notably habitat conditions and food quality, have a significant impact on shell growth, with higher nutrition supporting larger sizes.Pila celebensis (family Ampullariidae) is a native freshwater snail species found in Asia, including Indonesia, and possesses significant ecological and economic importance. However, Pila populations face various threats due to the invasiveness of  Pomacea, as well as human activities. This study aimed to document the presence of P. celebensis on Madura Island and describe its morphological and morphometric characteristics. Samples were collected from four localities in Madura. All specimens had a similar morphological shell, including a spherical shell with a prominent brown color and dark brown spiral pattern, an oval to elongate lunar aperture, a thin or closed umbilicus, and a concentric operculum. However, morphometric size varied significantly by location. The largest individuals were found in the rice fields of South Poter Village, while the smallest were found in a stream in Nyalabuh Laok Village. This difference reveals that environmental factors, notably habitat conditions and food quality, have a significant impact on shell growth, with higher nutrition supporting larger sizes.